2022
DOI: 10.1155/2022/1915185
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Analysis in Bidirectional Hybrid Nanofluid Containing Nanospheres with Variable Thermal Activity

Abstract: An investigation of the thermal performance of water-conveying nanospheres (magnetite ( Fe 3 O 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Furthermore, it has been discovered that non‐Newtonian behavior (Williamson fluid) boosts the temperature and the concentration profile of nanoparticles while causing a decrease in fluid velocity. Ahmad et al 15 discussed the entropy study in a bidirectional hybrid nanofluid comprising nanospheres with changing thermal activity. They found that the temperature‐controlling indices also influence the thermal profile, which diminishes as these indices are given more weight.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been discovered that non‐Newtonian behavior (Williamson fluid) boosts the temperature and the concentration profile of nanoparticles while causing a decrease in fluid velocity. Ahmad et al 15 discussed the entropy study in a bidirectional hybrid nanofluid comprising nanospheres with changing thermal activity. They found that the temperature‐controlling indices also influence the thermal profile, which diminishes as these indices are given more weight.…”
Section: Introductionmentioning
confidence: 99%
“…Solar reflectance greater than 95% requires a thickness of 160 m. Sweat wicking and drying are hindered. A major personal thermoregulation pathway, moisture management, in hot, humid, and sunny conditions, is essential to wick sweat away from skin and evaporate it quickly so that heat can be dissipated, and the body can cool safely [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Iftikhar et al [43] inspected the heat transference of blade-formatted cadmium telluride-graphite nanocomposites hybrid nanofluid flow under electromagnetohydrodynamics. Iftikhar et al [44] studied an entropy creation of sphere-sized bidirectional hybrid nanofluid along with varying thermal performance. Using the Williamson model, Hussain [45] investigated the viscous dissipation, thermal radiation, and entropy creation of a hybrid nanofluid (Cu-graphene oxide/sodium alginate) that was situated within solar airplane wings and moved into a trough with a parabolic form.…”
Section: Introductionmentioning
confidence: 99%